Analisis Rantai Pasokan pada Industri Furnitur Rotan Berbasis Ekspor di Kabupaten Cirebon - Renaldy Dwityo Adiputra; Ratna Arifianti; Muhammad Naufal Luthfi; Dedi Muhammad Siddiq (Paradigma Agribisnis, 2024)
The rattan industry in Cirebon Regency is known and liked by local consumers and foreign consumers. As an export-based industry that has abundant sources of raw materials, Indonesian rattan furniture industry has only been able to meet a small share of the world market. To be able to reach this potential, this industry must have excellence in carrying out its operational activities, especially in terms of supply chain management. The purpose of this study is to analyze how the implementation of an effective supply chain management model in one exportbased rattan furniture company in Cirebon Regency. This research was conducted using a qualitative method by interviews 10 respondents from internal and external sources who have roles in supply chain management activities in this company. Researchers can conclude that the implementation of supply chain management in the sample company has been systematic and strategic at every stage of its operations. The ERP system is recommended to be used by company to avoid problems that may arise from manual systems, as well as to make operational implementation more efficient. The development of human resources and craftsmen needs to be carried out continuously considering this industry is a labor-intensive industry. Cooperation with external parties such as the government and associations also need to be continuously forged to achieve stability in the availability of human resources of this industry.Keyword: Supply Chain Management and Rattan Industry